Community Assistance to Improve the Ability to Use Basic Unity and Virtual Reality - Herawati Yusuf; Novie Theresia Br. Pasaribu; Erwani Merry Sartika; Evan Adrian Adhi; Reynaldy Felicius Gunawan; Richard Setiawan; Dion Melvern Siswanto; Vieri Candhya Wigayha; Nathaniel Pius Winata; Markus Tanubrata; Rainisa Maini Heryanto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
During the pandemic of Corona Virus Disease 2019 (COVID-19) that hit Indonesia, all activities were very limited. Electrical Engineering Study Program of Universitas Kristen Maranatha was motivated to share knowledge especially in the field of science about